Near-Instantaneously Self-Healing Coating toward Stable and Durable Electromagnetic Interference Shielding - Zou, Lihua; Lan, Chuntao; Zhang, Songlin; Zheng, Xianhong; Xu, Zhenzhen; Li, Changlong; Yang, Li; Ruan, Fangtao; Tan, Swee Ching (Nano-Micro Letters, 2021)
Durable electromagnetic interference (EMI) shielding is highly desired, as electromagnetic pollution is a great concern for electronics’ stable performance and human health. Although a superhydrophobic surface can extend the service lifespan of EMI shielding materials, degradation of its protection capability and insufficient self-healing are troublesome issues due to unavoidable physical/chemical damages under long-term application conditions. Here, we report, for the first time, an instantaneously self-healing approach via microwave heating to achieve durable shielding performance. First, a hydrophobic 1H,1H,2H,2H-perfluorooctyltriethoxysilane (POTS) layer was coated on a polypyrrole (PPy)-modified fabric (PPy@POTS), enabling protection against the invasion of water, salt solution, and corrosive acidic and basic solutions. Moreover, after being damaged, the POTS layer can, for the first time, be instantaneously self-healed via microwave heating for a very short time, i.e., 4 s, benefiting from the intense thermal energy generated by PPy under electromagnetic wave radiation. This self-healing ability is also repeatable even after intentionally severe plasma etching, which highlights the great potential to achieve robust and durable EMI shielding applications. Significantly, this approach can be extended to other EMI shielding materials where heat is a triggering stimulus for healing thin protection layers. We envision that this work could provide insights into fabricating EMI shielding materials with durable performance for portable and wearable devices, as well as for human health care. Highlights: 1 Stable and durable electromagnetic interference (EMI) shielding performance was achieved in harsh environments by applying a thin protective coating of hydrophobic 1H,1H,2H,2H-perfluorooctyltriethoxysilane (POTS) on polypyrrole (PPy)-modified fabrics. 2 The damaged POTS layer can be instantaneously self-healed ( 4 s) for the first time by the microwave heating effect of PPy. 3 The self-healing process is repeatable even after severe damages, highlighting the great potential to exploit EMI shielding materials’ instant microwave heating effects to enable robust and durable EMI shielding applications.